1993
DOI: 10.1111/j.1365-3040.1993.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing sensitivity to light and nitrate but not to gibberellins regulates seasonal dormancy patterns in Sisymbrium officinale seeds

Abstract: Seeds of Sisymbrium officinale (L.) Scop, that are buried under natural conditions in soil pass annually through a seasonal pattern of changes in dormancy. Dormancy is broken in autumn-winter and re-induced in summer. To elucidate dormancy regulation in this species under natural conditions, a detailed analysis of the changes in sensitivity to some relevant germination factors was carried out Germination data fitted as logistic dose response curves showed that sensitivity to light and nitrate, both indispensab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 35 publications
4
60
0
1
Order By: Relevance
“…Furthermore it has been shown that the rate of increase of sensitivity to environmental signals was not fixed, seeds produced in different years had a different response. This is consistent with the fact that the depth of dormancy is not only determined genetically, but also by the ambient environment during seed formation (Donohue, 2005).Non-dormant seeds that are exposed for some time to unfavourable germination conditions (imbibed seeds kept at relatively high temperature in darkness for example) may enter a state of dormancy again, which is called secondary dormancy (Cone and Spruit, 1983;Derkx and Karssen 1993b; Hilhorst, 2007).A challenge in dormancy and germination research is to identify the nature of the crucial regulator(s) that prevent(s) the onset of germination (dormancy), that trigger(s) the germination process and their mutual interaction. Furthermore, it is important to know how the environmental factors such as light and cold affect the endogenous factors that control germination.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore it has been shown that the rate of increase of sensitivity to environmental signals was not fixed, seeds produced in different years had a different response. This is consistent with the fact that the depth of dormancy is not only determined genetically, but also by the ambient environment during seed formation (Donohue, 2005).Non-dormant seeds that are exposed for some time to unfavourable germination conditions (imbibed seeds kept at relatively high temperature in darkness for example) may enter a state of dormancy again, which is called secondary dormancy (Cone and Spruit, 1983;Derkx and Karssen 1993b; Hilhorst, 2007).A challenge in dormancy and germination research is to identify the nature of the crucial regulator(s) that prevent(s) the onset of germination (dormancy), that trigger(s) the germination process and their mutual interaction. Furthermore, it is important to know how the environmental factors such as light and cold affect the endogenous factors that control germination.…”
supporting
confidence: 71%
“…Non-dormant seeds that are exposed for some time to unfavourable germination conditions (imbibed seeds kept at relatively high temperature in darkness for example) may enter a state of dormancy again, which is called secondary dormancy (Cone and Spruit, 1983;Derkx and Karssen 1993b;Hilhorst, 2007).…”
Section: Seed Developmentmentioning
confidence: 99%
“…However, they do not really compete, because full induction of dormancy in buried seeds takes several months, while germination is completed in a few days. Derkx & Karssen (1993a) showed that when Sisymbrium officinale seeds are buried in darkness germination is prevented. However, the temperature they are exposed to regulates the changes in the requirements for light, nitrate and temperature for subsequent germination (i.e.…”
Section: Temperature (°C)mentioning
confidence: 99%
“…regulates dormancy). Changes in dormancy occur in spite of continuous darkness and are not correlated with changes in endogenous nitrate content (Derkx & Karssen 1993a). From experiments in which Sisymbrium officinale seeds were incubated in darkness, Derkx eta!.…”
Section: Temperature (°C)mentioning
confidence: 99%
See 1 more Smart Citation